Recommendations on Informational Monitoring of the Safety and Efficacy of Medicinal Products in the Russian Federation as Part of Pharmacovigilance - K. S. Milchakov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
Monitoring of information on the safety and efficacy of medicinal products that involves searching for data on benefits and risks of the post-approval use of medicinal products is one of the most important pharmacovigilance processes. The aim of the study was to summarise instruments and recommendations for effective monitoring of information on the safety and efficacy of medicinal products. The article presents the results of the analysis of the regulatory framework and modern tools for scientific literature and Internet information monitoring as part of routine pharmacovigilance. The main resources recommended for information monitoring are open-source scientific and medical bibliographic databases; scientific journals; websites of regulatory authorities and international organisations that monitor the efficacy and safety of medicines; social networks; and online patient communities. Drawing upon current regulatory documents and international good pharmacovigilance practices, the article presents recommendations on the number of resources needed for conducting qualitative monitoring and on the formulation and revision of a search strategy. It describes modern technological solutions in the field of information monitoring, substantiating the suitability of new achievements in such areas as Data Science and natural language processing (NLP) for marketing authorisation holders to collect and analyse data on the safety and efficacy of medicinal products. Regular updates of the search strategy and information channels, the use of software products for the automatic collection and analysis of data from various sources, and the creation of a continuous training system for pharmacovigilance specialists will allow for high-quality monitoring of information on the safety and efficacy of medicines.